NON-DAIRY YOGHURT ENRICHED WITH FUNCTIONAL PLANT-BASED INGREDIENTS - A REVIEW - MUNTEANU-ICHIM Roxana-Andreea; MISU Georgiana Ancuta; CANJA Cristina Maria; LUPU Mirabela; BĂDĂRĂU Carmen-Liliana; PĂDUREANU Vasile; MATEI Florentina (Scientific Papers. Series D. Animal Science, 2024)
The paradigm surrounding milk has shifted as consumer preferences evolve due to lactose intolerance awareness and the prevalence of cow's milk allergies. Consequently, plant-based milk substitutes have gained popularity. This study offers a comprehensive examination of the physicochemical, rheological and sensory attributes of various functional plant-based yoghurts, coconut yoghurt with tapioca, fruits and soy yoghurt with red fruits, mango, lemon grass, etc. The study reveals the potential of these products to fulfil consumer demands for both sensory satisfaction and nutritional benefits. Furthermore, it identifies avenues for further refinement and innovation in product development and formulation, thereby providing valuable insights for both industry stakeholders and consumers seeking viable dairy alternatives. This study underscores the growing importance of plant-based options in meeting diverse dietary needs and preferences in today's evolving food scene. Moreover, it emphasizes the necessity of transitioning to a more plant based diet to address climate change, reduce environmental impacts, and improve healt
Keywords: functional; non-dairy yogurt; plant-based